THE ROLE OF CODE OF CONDUCT IN INFLUENCING GREEN INTELLECTUAL CAPITAL, CARBON ACCOUNTING, ANDCORPORATE GOVERNANCE TO FINANCIAL PERFORMANCE - Asri Zaldin; Evanita Husein (International Journal of Contemporary Accounting, 2024)
This research aims to determine the role of code of conduct in influencing green intellectual capital, carbon accounting and corporate governance on the financial performance. This research is focused on banking sector companies on the Indonesia Stock Exchange between 2016 until 2021. This study applied secondary data, namely annual reports. Saturated sampling is implied as a method for data collection. The total sample is 46 companies, generating 276 observations. The analytical method employed in this study was analysis by regression. The study finds that green intellectual capital disclosure, carbon accounting and corporate governance positively impacts financial performance, and using the code of conduct index as a moderating factor results in a positive effect on financial performance. As sustainability becomes a cornerstone of corporate strategy, organizations are challenged to integrate ethical frameworks that balance environmental stewardship with economic objectives. Additionally, the type of industry also influences financial performance. The research highlights that a well-established code of conduct not only facilitates the alignment of sustainability goals with financial objectives but also moderates and strengthens the pathways through which these practices influence financial performance. The study provides valuable insights for policymakers, regulators, and corporate leaders, emphasizing the necessity of ethical frameworks to achieve long-term financial viability and environmental sustainability.